Diarylheptanoids suppress proliferation of pancreatic cancer PANC-1 cells through modulating shh-Gli-FoxM1 pathway - Dong, Guang-zhi; Jeong, Ji Hye; Lee, Yu-ih; Lee, So Yoon; Zhao, Hui-Yuan; Jeon, Raok; Lee, Hwa Jin; Ryu, Jae-Ha (Archives of pharmacal research, 2017)
Pancreatic cancer is one of the leading causes of cancer, and it has the lowest 5-year survival rates. It is necessary to develop more potent anti-pancreatic cancer drugs to overcome the fast metastasis and resistance to surgery, radiotherapy, chemotherapy, and combinations of these. We have identified several diarylheptanoids as anti-pancreatic cancer agents from Alpinia officinarum (lesser galangal) and Alnus japonica . These diarylheptanoids suppressed cell proliferation and induced the cell cycle arrest of pancreatic cancer cells (PANC-1). Among them, the most potent compounds 1 and 7 inhibited the shh-Gli-FoxM1 pathway and their target gene expression in PANC-1 cells. Furthermore, they suppressed the expression of the cell cycle associated genes that were rescued by the overexpression of exogenous FoxM1. Taken together, (E)-7-(4-hydroxy-3-methoxyphenyl)-1-phenylhept-4-en-3-one ( 1 ) from Alpinia officinarum (lesser galangal) and platyphyllenone ( 7 ) from Alnus japonica inhibit PANC-1 cell proliferation by suppressing the shh-Gli-FoxM1 pathway, and they can be potential candidates for anti-pancreatic cancer drug development.